The Perception Of Road Pricing Policy (Rpp) In Georgetown, Penang - Mat, Abu Bakar (2018)
Urban traffic congestion is a significant problem which is happened in many parts of the world. Cities in Malaysia such as Klang Valley, Georgetown and Johore Bharu are facing serious urban traffic problem. The policies which are formulated to overcome this problem focusing on supply side of management; the construction of new roads, highway, fly-over and roads / highways widening. There are arguments by the experts that policy option must emphasis on demand side of management. A bold, radical and unpopular policy such as road pricing policy (RPP) from the instrument of Travel Demand Management (TDM) can be considered seriously. Land Public Transport Act 2010 outlines the proposal to establish road pricing policy within any designated area in Malaysia as a solution to reduce urban traffic congestion. Local Plan for Penang Island has outlined that the policy will be implemented in Georgetown as a tool to improve urban traffic congestion once an efficient public transport system is implemented. However, it seems that measure to work on the implementation of road pricing policy is not taken seriously. Therefore, this thesis examines the perception and acceptability of public/road users and policy makers in Georgetown, Penang, towards the introduction of road pricing policy. This research aims to analyse the problem of urban traffic congestion, perception, acceptability and implementation of road pricing policy (RPP). In this case, the experiences of big cities such as Singapore, London and Tokyo were examined to determine their strengths and weaknesses in implementing RPP. Mixed methods of quantitative and qualitative research were adopted to achieve the aims and objectives as outlined. Survey method was employed amongst the residents/road users and self-administered survey was applied amongst policy makers to explore their perceptions and attitudes towards the acceptability of RPP. The findings of this research have provided some insights on the barriers of acceptability towards road pricing policy such as the attitude of the road users and policy makers, the use of the revenue, unfairness to low income group, travelling behavior and design/layout issues. Besides that, there are successful factors identified if road pricing policy is introduced such as efficiency benefits, pressing traffic problem, alternative to the available policy, clear and transparent of aim and objectives. In short, the result of this research will contribute to the implementation of road pricing policy in Georgetown, Penang once the acceptability is gained from the public/road users and policy makers.